DEFINITION OF THE PLACE OF SHORT CIRCUITS ON POWER LINES OF 110 KV AND ABOVE ON INSTANTANEOUS VALUES OF CURRENTS AND VOLTAGES - N. S. Burjanina; K. P. Vasil'eva; J. F. Koroljuk; E. V. Lesnykh; K. V. Suslov (Известия высших учебных заведений: Проблемы энергетики)
It proposed a two-way method of determining the place of the short circuit in the power lines, using the instantaneous values of currents and voltages. This sampling interval is proposed equal to a quarter period of the mains frequency. With this range are excluded even harmonics and odd harmonics are calculated without distortion. Given that zero components in the currents and voltages can be eliminated schematics, low-pass filters can be performed with a cutoff frequency of 250 - 300 Hz. To determine the fault location is proposed to use the parameters of the direct and reverse sequences.